2009
DOI: 10.1002/cplx.20288
|View full text |Cite
|
Sign up to set email alerts
|

Common scaling laws for city highway systems and the mammalian neocortex

Abstract: A variety of scaling laws are known for the mammalian neocortex relating gray matter volume, total number of synapses [1,2], white matter volume [3][4][5][6][7][8][9], number of neurons [6,[10][11][12], surface area [4,5,[13][14][15][16], axon caliber [1,17], and number of cortical areas or compartments [18]. These neocortical scaling laws appear to be a consequence of selection pressure for a sheet-like structure (namely, gray matter) to economically maintain a high level of interconnectedness [1,2,19,20]. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Indeed, broad interdependence of disparate physiological tissues is a central theme of the multifractal tensegrity hypothesis and a main motivation for using multifractal geometry to make explicitly estimable the non-linear interactions governing a cohesive system across many scales (Ingber, 2006; Van Orden et al, 2012; Turvey and Fonseca, 2014). Indeed, the dawning picture we have of the nervous system suggests a causal relationship run by non-linear interactions across scale (Morgane et al, 2005; Changizi and DeStefano, 2009; Deco et al, 2011). To the point, beyond muddying our ability to identify clear parts with reliably stable and distinct responsibilities, these non-linear interactions appear to be the very physiological support that allows the nervous system to operate as impressively as it does.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, broad interdependence of disparate physiological tissues is a central theme of the multifractal tensegrity hypothesis and a main motivation for using multifractal geometry to make explicitly estimable the non-linear interactions governing a cohesive system across many scales (Ingber, 2006; Van Orden et al, 2012; Turvey and Fonseca, 2014). Indeed, the dawning picture we have of the nervous system suggests a causal relationship run by non-linear interactions across scale (Morgane et al, 2005; Changizi and DeStefano, 2009; Deco et al, 2011). To the point, beyond muddying our ability to identify clear parts with reliably stable and distinct responsibilities, these non-linear interactions appear to be the very physiological support that allows the nervous system to operate as impressively as it does.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, it has been elucidated that urban indicators quantifying city activities on average scale with the population size in a power-law manner. These include many creative productivities and infrastructure volumes [14][15][16][17] such as the gross domestic product (GDP), the number of patents, human online activities [18], prosocial behaviors [19], quantities related to highway systems [20], the number of crimes [21], the number of supply stations [22], and emissions of CO 2 [23] and NO 2 [24]. There exist several models explaining such allometric scaling behavior [25][26][27][28] and fluctuations around average power-law relations [29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Changizi [24] found that the brain and the city both connect much more intensively to function more optimally as they grow bigger, and they both follow similar experiential principles (Scaling laws). Wedeen [25] has suggested a new view of the structure of a brain starts that sees it as a simple, elementary structure with MRI analysis, and it is similar to New York City's street grids that are directed to a particular object.…”
Section: Relationship Between the City And The Complex Systemmentioning
confidence: 98%